The Didactic Values in The Novel Of 9 Summers 10 Autumns - Rahmita Sari; Surastina Surastina; Akhmad Sutiyono; Tri Riya Anggraini (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2018)
This study aims to describe the didactic values ​​of the novel